The impact of COVID-19 on global health journals: an analysis of impact factor and publication trends - Hao Li; Don Eliseo Lucero-Prisno; Jiaxin He; Xinliang Liu; Xinyang Lu; Meiling Zhong; Changli Jia; Zheng Feei Ma (BMJ Global Health)
Background COVID-19 has affected research productivity across all areas of knowledge. Current evidence suggests that COVID-19 has had a blockbuster effect on journal impact factors (JIFs) and publication trends, while little is known on global health journals.Methods Twenty global health journals were included to analyse the impact of COVID-19 on their JIFs and publication trends. Indicator data, including numbers of publications, citations, articles with different types, etc, were extracted from journal websites and Web of Science Core Collection database. The JIFs from 2019 to 2021 were simulated for longitudinal and cross-sectional analyses. Interrupted time-series analysis and non-parametric tests were applied to assess whether COVID-19 had decreased non-COVID-19 publications from January 2018 to June 2022.Results In 2020, 615 out of 3223 publications were COVID-19 related, accounting for 19.08%. The simulated JIFs of 17 out of 20 journals in 2021 were higher than those in 2019 and 2020. Notably, 18 out of 20 journals had a decrease in their simulated JIFs after excluding COVID-19-related publications. Moreover, 10 out of 20 journals decreased their monthly numbers of non-COVID-19 publications after the COVID-19 outbreak. For all the 20 journals as a whole, after the COVID-19 outbreak in February 2020, the total number of non-COVID-19 publications significantly decreased by 14.2 compared with the previous month (p=0.013), and since then, on average, the publications had decreased by 0.6 per month until June 2022 (p<0.001).Conclusions COVID-19 has impacted the structure of COVID-19-related publications, the JIFs of global health journals and their numbers of non-COVID-19 publications. Although journals may benefit from increased JIFs, global health journals should avoid relying on a single metric. More follow-up studies including more years of data with a combination of metrics should be conducted to generate more robust evidence.